Interpretation of the Meaning of the Companions of the Prophet in the Book of Ash Shaksiah Al Islamiyah by Taqiyuddin An-Nabhani - Malik Akbar Simanullang; Romlah Abubakar Askar; Abdul Ghofur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to analyze the interpretation of the meaning of the prophet’s companions in Islamic history. Then in this book, various aspects of Islamic personality are explained, including the meaning of the companions of the Prophet. The method used in this study is a qualitative method, with a literature review in the hadith book. And the results of this study show that there are various views from hadith scholars about Who is included in the term friend of the prophet?. There are those who believe that the friend of the messenger of Allah is someone who lived in the time of the prophet and only saw the messenger of allah, and there are also those who believe that the friend of the messenger of allah is someone who has met the prophet person, not just seen him. And hopefully this research will provide a better contribution so that we can find out who is among the companions of the Prophet Muhammad.